Dairy Farmers Perception on Cooperatives in East Java, Indonesia - Hery Toiba; Rachman Hartono; Dwi Retnoningsih; Moh. Shadiqur Rahman (HABITAT, 2021)
Although past studies have shown that cooperatives can improve the welfare of rural communities. However, many farmers did not aware about the cooperative advantages. This begs a question as to whether cooperatives really contribute to the rural incomes and economies. This study aims to assess farmers’ perception on cooperative membership and how members have adopted innovative technologies. Data were obtained from a survey with 300 dairy farmers in Malang and Batu, East Java. The data were examined using a descriptive analysis. The results showed that farmers who do not join any cooperatives perceive that the institution is not able to determine the quality of their milk produce. Meanwhile, farmers who are members of a cooperative perceive that the institution can maintain stability of milk produce’s sales prices. This implies that education about cooperatives among farmers needs to be improved so that they can objectively view the benefits of cooperative membership and make informed decision in their economic activities.